Assessing health literacy among adult outpatients attending allied health clinics in western sydney: A cross‐sectional survey using a multidimensional instrument. (31st January 2021) - Hobbs, Kim; Muscat, Danielle Marie; Ceprnja, Dragana; Gibson, Jodi‐Anne; Blumenthal, Caron; Milad, Rula; Burns, Chris; Dennis, Sarah; Lau, Timothea; Flood, Victoria
Abstract: Issue addressed: Low health literacy disproportionately affects adults from culturally and linguistically diverse backgrounds. This study investigated the health literacy of adults attending outpatient allied health services in western Sydney, a highly diverse region in Sydney with residents from a range of cultural and linguistic backgrounds. Methods: A cross‐sectional survey was undertaken between March and April 2017 using the Health Literacy Questionnaire (HLQ). Participants, aged over 18 years and with a primary language of English, Arabic, Chinese or Hindi, were recruited from outpatient allied health clinics at Westmead Hospital. Means (standard deviation) for each of the nine HLQ domains were calculated and associations with demographic variables were investigated using analysis of variance (ANOVA). Results: Two hundred and thirty people were included with mean age of 45.1 years (SD = 19.0), the majority were female (75.5%), over half were born overseas (55.7%) and 77.6% reported speaking English at home. The highest mean score on a HLQ domain (out of 5) was "Understanding health information well enough to know what to do" (M = 4.19; SD = 0.67), and the lowest mean score (out of 4) was "Appraisal of health information" (M = 2.97; SD = 0.54). Participants who did not speak English at home had significantly lower scores on seven of the nine HLQ domains. Conclusions: Important health literacy strengths and limitations of a diverse sample of adults attending outpatient allied health services in western Sydney were identified. Findings should be considered in the light of the cross‐sectional survey methodology with non‐random sampling. So what: Data will inform future interventions to improve health literacy and health outcomes among vulnerable population groups in western Sydney.